IMPROVING THE ORGANIZATIONAL AND ECONOMIC MECHANISMS FOR ENSURING ENVIRONMENTAL SECURITY IN THE SUSTAINABLE DEVELOPMENT OF REGIONAL ECONOMIES (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
This article analyzes the economic and organizational foundations of ensuring environmental security at the regional level. The study evaluates the role of environmental protection factors in achieving the sustainable development of regional economies through a scientific and systematic approach. In particular, it substantiates the necessity of viewing environmental security as an integral part of economic policy and aligning it with regional planning strategies. The article highlights key environmental challenges such as air pollution, industrial waste, and inefficient use of natural resources as significant barriers to consistent regional economic growth. It further emphasizes the need for institutional reforms, the improvement of environmental financing mechanisms, and the implementation of green economy principles to ensure environmental security. It is scientifically argued that the integration of regional environmental policy with economic instruments such as tax incentives, grants, and environmental standards can yield positive outcomes. The concluding section outlines prospects for enhancing investment attractiveness and social well-being through improved environmental security and ends with a set of targeted policy recommendations.